Ataxin-2, Twenty-four, and Dicer-2 are components of a noncanonical cytoplasmic polyadenylation complex. - Nadimpalli, H.P.; Guitart, T.; Coll, O.; Gebauer, F. (Life science alliance, 2022)
Cytoplasmic polyadenylation is a mechanism to promote mRNA translation in a wide variety of biological contexts. A canonical complex centered around the conserved RNA-binding protein family CPEB has been shown to be responsible for this process. We have previously reported evidence for an alternative noncanonical, CPEB-independent complex in Drosophila, of which the RNA-interference factor Dicer-2 is a component. Here, we investigate Dicer-2 mRNA targets and protein cofactors in cytoplasmic polyadenylation. Using RIP-Seq analysis, we identify hundreds of potential Dicer-2 target transcripts, ?60% of which were previously found as targets of the cytoplasmic poly(A) polymerase Wispy, suggesting widespread roles of Dicer-2 in cytoplasmic polyadenylation. Large-scale immunoprecipitation revealed Ataxin-2 and Twenty-four among the high-confidence interactors of Dicer-2. Complex analyses indicated that both factors form an RNA-independent complex with Dicer-2 and mediate interactions of Dicer-2 with Wispy. Functional poly(A)-test analyses showed that Twenty-four and Ataxin-2 are required for cytoplasmic polyadenylation of a subset of Dicer-2 targets. Our results reveal components of a novel cytoplasmic polyadenylation complex that operates during Drosophila early embryogenesis.